Structural and relaxor behavior in lead-free (Ba0.8Sr0.2)Ti1−x(Zn1/3Nb2/3)xO3 ceramics. Issue 6 (1st May 2016) - Dhifallah, Nabil; Turki, Olfa; Marssi, Mimoun El; Dammak, Mohamed; Khemakhem, Hamadi
Abstract: The Solid solutions of (1− x )Ba0.8 Sr0.2 TiO3 − x Ba(Zn1/3 Nb2/3 )O3 (BST–BZN) with 0.025≤ x ≤0.15 were prepared by a high temperature solid-state reaction technique. The effects of the Ba(Zn1/3 Nb2/3 )O3 addition on the phase composition in the B site on structural and dielectric properties was investigated. The room temperature X-ray diffraction analyses of all ceramics revealed a perovskite phase with a composition dependent symmetry. The temperature and frequency dependence of the dielectric permittivity and losses have been explored. While ceramics of compositions x ≤0.05 showed normal ferroelectric behavior, while ceramics with x ≥0.1 were of relaxor type. It was found that degree of diffuseness and the relaxor effect increased, whereas the transition temperature ( T C or T m ) decreased when both zinc and niobium were introduced in the Ba0.8 Sr0.2 TiO3 lattice. For the composition with x ≥0.1, the frequency depend on T m, satisfying the Vogel–Fulcher formula, which indicates a relaxor bahavior.